Serum creatinine to cystatin C ratio and clinical outcomes in adults with non-dialysis chronic kidney disease - Hyun, Young Youl; Lee, Kyu-Beck; Kim, Hyoungnae; Kim, Yaeni; Chung, Wookyung; Park, Hayne Cho; Han, Seung Hyeok; Oh, Yun Kyu; Park, Sue Kyung; Oh, Kook-Hwan (Frontiers in Nutrition, 2022)
ABSTRACT Background: Studies have suggested that the serum creatinine/cystatin C (Cr/CysC) ratio is a surrogate marker for muscle wasting and is associated with adverse outcomes in several disease conditions. To clarify the utility of the Cr/CysC ratio as a prognostic marker in chronic kidney disease (CKD), we evaluated the association between the Cr/CysC ratio and clinical outcomes in patients with non-dialysis CKD. Methods: This prospective observational cohort study included 1,966 participants of the KoreaN cohort study Outcomes in patients With CKD (KNOW-CKD). We evaluated associated factors with the serum Cr/CysC ratio and association between the serum Cr/CysC ratio and composite outcomes of all-cause death and cardiovascular events Results: The mean age was 54  12 (SD) years and 61% were men. The mean serum Cr/CysC ratio was 10.97  1.94 in men and 9.10  1.77 in women. The Cr/CysC ratio correlated positively with urinary creatinine excretion, a marker of muscle mass. In the fully adjusted Cox proportional hazard model, the Cr/CysC ratio was associated with the occurrence of adverse outcomes through a median follow-up of 5.9 years [hazard ratio (HR) = 0.92, 95% confidence interval (CI) = 0.850.99 for the composite outcomes, HR = 0.87, 95% CI, 0.780.97 for all-cause death, and HR = 0.93; 95% CI, 0.841.04 for cardiovascular events]. In subgroup analyses, there were interactions of the Cr/CysC ratio with age and sex for risk of the clinical outcomes, but not eGFR group. Conclusions: A higher Cr/CysC ratio is associated with a lower risk of the composite outcomes, especially all-cause mortality, even after adjusting for eGFR. These suggest that the Cr/CysC ratio is a useful prognostic marker in CKD.